A new taxonomic system of the Campanulaceae s.s. Issue 3 (30th January 2015) - Hong, De‐Yuan; Wang, Qiang
Abstract The Campanulaceae s.s. have been proved to be monophyletic, but the subdivision of the family is still controversial among authors. To investigate the intrafamilial structure of the Campanulaceae s.s., four chloroplast DNA fragments, atpB, matK, rbcL, and petD with the petB‐petD spacer region, were chosen for molecular phylogenetic analysis, and 90 taxa representing 36 genera of this family were sampled. The result shows that the Campanulaceae s.s. consist of three strongly supported monophyletic clades. This result is highly correlated with the data from palynology and external morphology. Therefore, we propose to establish a new three tribal classification system of Campanulaceae s.s. The Cyanantheae is characterized by colpate or colporate pollen with elongate apertures and a loculicidal capsule which is dehiscent by apical valves, or a berry. The other two tribes have porate pollen with poroid apertures, but the Campanuleae possesses a poricidal capsule which is dehiscent by lateral pores or valves, or a dry indehiscent fruit, whereas the Wahlenbergieae possesses a loculicidal capsule which is dehiscent by apical valves, pores, or opercula. In the Cyanantheae, we recognize 6 subtribes and 10 genera. In addition, keys to tribes of Campanulaceae s.s. and to subtribes and genera of the Cyanantheae are presented.